(untitled) (Philological Studies, 2020)
Even though Lev Nikolayevich Tolstoy is mostly known as an opponent of (female) sexuality, this essay argues that female narcissism is an equally controversial category. As plots of three texts – the novellas “The Kreutzer Sonata” and “Family Happiness”, and the novel Anna Karenina – show, female characters have to convert ego-libido into object-libido in order to, while overcoming disappointment, reach Tolstoy’s idea of living for others. The first part of the essay is based on a close reading of Tolstoy’s novellas, and the second part examines the female characters of Anna Karenina. Instead of pointing out the differences between Kitty, Dolly and Ana, I am trying to foreground the ways in which they reflect each other, while linking Anna’s intertextual representations, two portraits, to Tolstoy’s remarks on the social function of art.